Elaboración de Material Concreto para la Enseñanza-Aprendizaje de Conjuntos - Quinaluiza Arias, Evelin Lissette (2024)
The research work addresses the topic of “Development of Concrete Material for the Teaching-Learning of Sets”. Its objective is to design a didactic guide for using concrete material in the teaching-learning of sets among first-semester students of the Pedagogy of Experimental Sciences: Mathematics and Physics at the National University of Chimborazo. A methodology with a quantitative approach and a non-experimental design was applied. Data collection techniques included an objective test administered to 34 first-semester students and an interview with the course instructor. The results showed that 57% of the students do not master the basic concepts of sets, and 59% have difficulty applying these theoretical contents in practical exercises. The interviewed instructor indicated that students have difficulties learning and identifying sets conceptually and graphically and mentioned that if concrete materials were available at the university, she would implement them as a didactic resource. For this reason, a concrete material guide was developed, which includes relevant activities and exercises, aiming to prepare students in a meaningful way and provide a resource that contributes to the development of competencies in future professionals.